1999
DOI: 10.1243/0954405991517065
|View full text |Cite
|
Sign up to set email alerts
|

A design reuse system

Abstract: Successful past design is the largest accumulation of expertise in the entire manufacturing sector and effective exploitation needs to structure this store of information. This paper shows that the design model under which this information is going to be used greatly influences the structuring process. Within design function deployment past designs should be structured as (a) a product concept, (b) a solution concept, (c) an embodiment design and (d) a detailed design, for efficient reuse. Illustrative example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…Design ruse approaches to that are based on a design methodology (Shahin et al, 1999) (Blessing 1995) structure the elements of the system around the conceptual framework specified by the design methodology (typically systematic design). Methodology based approaches are best suited to fundamental design problems, where existing solutions are not available: variant design could apply a more structured and specific method to reuse previous solutions.…”
Section: Current Research On Design Knowledge Reusementioning
confidence: 99%
“…Design ruse approaches to that are based on a design methodology (Shahin et al, 1999) (Blessing 1995) structure the elements of the system around the conceptual framework specified by the design methodology (typically systematic design). Methodology based approaches are best suited to fundamental design problems, where existing solutions are not available: variant design could apply a more structured and specific method to reuse previous solutions.…”
Section: Current Research On Design Knowledge Reusementioning
confidence: 99%
“…Shahin et al [27] proposed to structure a systematic method that encompasses each stage of the design process. They identified that designs for reuse needed to be stored and retrieved either partially or wholly and, as such, the design reuse system must be integrated within a complete systematic design process.…”
Section: Design Reuse System By Shahin Andrews and Sivaloganathanmentioning
confidence: 99%
“…Design methodology has a certain guiding significance for the idea of design reuse, and some design methodology itself can be used as a reuse method. [3][4] Wu Shoufei introduced the concepts of family, standardization and serialization into the design reuse process through the research on the reuse strategy under the mass customization environment to meet the purpose of design diversification. [5][6] Based on the above problems, this paper proposes a function-driven design reuse method to reuse existing design information from existing model instances in the current market.…”
Section: Introductionmentioning
confidence: 99%